PEMETAAN PENGETAHUAN PENGGUNAAN TAPEL PERUT BAGI IBU PASCA MELAHIRKAN: Belly tape;, Strecth marks; Maternity; Pregnancy - Alfi Laili (Universitas Prima Indonesia, 2020)
Traditional medicine used within maternity care functions to recover reproduction system in order to get recobered as used to be ( before maternity). Maternity care period such as urgent transition period for mother's, babies and their family physiologically,social and emotionally. The condition that impacts such pain and death of mothers and baby risks commonly within maternity care in this period. However,todays in developed country,main attention towards mothers nd babies are only during pregnancy and deliver birth period. Moreover, within childbirth period mothers commonly complained about stomach pain (womb), over tired, strechty body and distended and also stretch marks. This study is a descriptive quantitative research. The population of this study is married woman who have got babies in Medan. They are 100 women. The sample was taken by purposive sampling method. It is choosing the women purposively because they have used to treat it with in childbirth period. It was 74 women. The data was collected by addressing questionnaire about Tapel knowledge such as definiton, understanding the benefits,the way to use and the functions. The lowest knowledge about it was repondents with education Senior high school 66,7%, callworling mothers (34,6%) and they arr 30-34 years old (34,8%). Furthermore, women who knows the way to treat Tapel correctly 54,1%. This finding shows that it is very important to do an action to improve itin order to avoid abuse that impact pain so hard.